Measuring performance in analytical measurements - Papastefanou, Hara; Eleftheriou, Polyvios (My University, 2009)
This paper presents the experience from a research which was conducted, within the framework of an EU project, on the various aspects of nutritional micronutrient measurements in foods. The project examined various methods of measuring basic micronutrients in food and water, their effectiveness, their difficulties, their costs as well as other elements. Data from a number of inter-laboratory comparison providers and prepared questionnaires were collated and analyzed, and the data gathered revealed that there are major differences in the methods employed and the instrumentation used. Methods using state of the art equipment such as ICP/MS and GC/MS were used for micronutrient measurements, and the results (successes and failures (z > 2) in the measurements) are presented. The laboratories from which data were gathered were mainly from across Europe (results for more than 700 laboratory determinations are presented), and the failures range from 0 to 67% of the measurement laboratories.
Keywords: Uncertainty; Measurement; Trace elements in nutrition